Penulisan Karya Ilmiah dalam Pengembangan Profesi Guru di SMPN Sentani Kabupaten Jayapura - I.Y Palit, Epiphani; Hutabarat, Ida Mariati; Gultom, Monika (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
The training of scientific writing is one of the efforts to develop teacher’s professionalism in SMP 2 and SMP 7 Sentani . This training aims to (1) equip teachers in writing scientific papers correctly based on the writing guidelines, (2) provide teachers the procedures of publishing scientific papers in journals, and (3) help teachers in analyzing data using SPSS software. The training used method of lecturing, discussing, demonstrating and practicing. After the training, participants practiced writing scientific papers assisted by the PKM Team. The result of the training found that the participants were satisfied indicated by the their enthusiastic presence in each meeting of the training. Supporting factors of implementation of this PKM are (1) the availability of resources of the TEAM, (2) the enthusiasm of the participants, (3) the support of the school principals, and (4) supporting funds from Kemenristek Dikti.